2019
DOI: 10.1167/iovs.19-27449
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lens Capsule Stability Using Capsular Tension Ring, Iris Retractor, and Capsule Expander Using a Porcine Model With Zonular Dehiscence

Abstract: Citation: Yaguchi S, Yaguchi S, Bissen-Miyajima H. Evaluation of lens capsule stability using capsular tension ring, iris retractor, and capsule expander using a porcine model with zonular dehiscence. Invest Ophthalmol Vis Sci. 2019;60:3507-3513. https:// doi.org/10.1167/iovs.19-27449PURPOSE. We evaluate the efficacy of capsular tension rings (CTRs), iris retractors (IRs), and capsule expanders (CEs) in stabilizing the lens capsule under different degrees of zonular dehiscence using a porcine model. METHODS.We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
(14 reference statements)
0
5
0
3
Order By: Relevance
“…Yaguchi et al demonstrated that use of the experimental porcine eye model with zonular dehiscence allows observation of the entire configuration of the lens capsule, and they also demonstrated differences in the efficacy of capsular bag retention with a CTR and CE [ 17 ]. In our current study, we demonstrated that with SSV, we were able to observe the intraoperative lens, the anterior chamber dynamics, and the three-dimensional movement of the capsular bag in the zonular fiber defect model.…”
Section: Discussionmentioning
confidence: 99%
“…Yaguchi et al demonstrated that use of the experimental porcine eye model with zonular dehiscence allows observation of the entire configuration of the lens capsule, and they also demonstrated differences in the efficacy of capsular bag retention with a CTR and CE [ 17 ]. In our current study, we demonstrated that with SSV, we were able to observe the intraoperative lens, the anterior chamber dynamics, and the three-dimensional movement of the capsular bag in the zonular fiber defect model.…”
Section: Discussionmentioning
confidence: 99%
“…The eye model of ZD was first created under the operating microscope using the technique that we previously reported in both porcine and human eyes. 6,7 The anterior chamber was filled with an ophthalmic viscosurgical device (OVD; Provisc; Alcon Vision, LLC, Fort Worth, TX); the entire iris root and the planned range of the ZD were dissected using capsule diathermy (CD-1000, Tagawa Electronic Research Institute, Chiba, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…We created a unique porcine eye model of ZD to observe the lens capsule and the crystalline lens during phacoemulsification 6,7 and adapted this eye model for the current study. Our primary and secondary objectives, respectively, were to observe the relationship between the quality of the capsulotomy and the range of ZD in porcine eyes and confirm the effectiveness of FL-assisted capsulotomy in human cadaver eyes with ZD.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental study with artificially induced varying grade zonular defects in pigs eyes, using iris retractors and CTR during surgery for stabilisation of the capsular bag, convincing statistically significant maintenance of the capsular bag's form was established compared with the control group, as well as statistically significant reduced entry of lens core fragments in the vitreous body (Yaguchi et al, 2019). The capsule's tension ring was implanted in most cases prior to phacoemulsification, so that the contour of the capsular bag of the subluxated lens was maintained during surgery, providing a function as a barrier between the eye's anterior and posterior segment and reducing the risk of tearing of the remaining zonule (Cionni & Osher, 1998;Cionni et al, 2003;Georgopoulos et al, 2007;Gimbel et al, 1997;Vasavada et al, 2012a).…”
Section: Shah Et Al Reported About 59 Cases Of Traumatic Subluxated Lenses In Larkanamentioning
confidence: 97%
“…Even though the phacoemulsification method does not differ in the sense of visual acuity and postoperative complications from other contemporary lens subluxation surgery methods (for example, pars plana lentectomy with scleral fixation of the intraocular lens (IOL)) (Thapa et al, 2016), it does include several advantages within itmore surgeons (cataract surgery) are familiar with the method, there is more phacoemulsification equipment, a shorter period for learning the method, simpler additional instruments and auxiliary devices (capsular and iris hooks, capsular tension rings (CTR) and segments), the use of which is consequently easier to learn, a shorter surgery time (Thapa et al, 2016), as well as lower surgical costs compared to other methods. The introduction of additional instruments and auxiliary devices should also be noted, starting from capsular tension rings which appeared in 1991 (Hara et al, 1991;Nagamoto & Bissen-Miyajima, 1994) until their evolution into the CTR concept which is used nowadays (Legler et al, 1993), design variations in 2007 (Henderson Ring) (Henderson & Kim, 2007), application of the modified CTR (Cionni Ring and mCTR) from 1998 (Cionni & Osher, 1998), improvement of the design associated with Malyugin in 2012 (Malyugin B, 2012), use of the iris retractors in lens subluxation surgery from 1997 (Novak, 1997) and its gradual development in subsequent decades (Yaguchi et al, 2011(Yaguchi et al, , 2019.…”
Section: Importance Of the Thesismentioning
confidence: 99%